2020
DOI: 10.48550/arxiv.2009.14802
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cocycle Enhancements of Psyquandle Counting Invariants

Abstract: We bring cocycle enhancement theory to the case of psyquandles. Analogously to our previous work on virtual biquandle cocycle enhancements, we define enhancements of the psyquandle counting invariant via pairs of a biquandle 2-cocycle and a new function satisfying some conditions. As an application we define new single-variable and two-variable polynomial invariants of oriented pseudoknots and singular knots and links. We provide examples to show that the new invariants are proper enhancements of the counting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The authors showed that the corresponding notion of psyquandle colorings of an oriented singular link, or pseudolink, determines a counting invariant. Furthermore, in [12], the authors gave a cocycle enhancement theory to the case of psyquandles. Precisely, they defined enhancements of the psyquandle counting invariant via pairs of a biquandle 2-cocycle and a new function satisfying some conditions.…”
Section: Psyquandles and Singular Link Invariantsmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors showed that the corresponding notion of psyquandle colorings of an oriented singular link, or pseudolink, determines a counting invariant. Furthermore, in [12], the authors gave a cocycle enhancement theory to the case of psyquandles. Precisely, they defined enhancements of the psyquandle counting invariant via pairs of a biquandle 2-cocycle and a new function satisfying some conditions.…”
Section: Psyquandles and Singular Link Invariantsmentioning
confidence: 99%
“…In this section we will provide an overview of results obtained for signular knots from psyquandles. The following definition was initially introduced in [25], but was reformulated in [12]. We will present the reformulated version of the definition.…”
Section: Psyquandles and Singular Link Invariantsmentioning
confidence: 99%
See 3 more Smart Citations